Impact of nuclearity and topology on the single molecule magnet behaviour of hexaazatrinaphtylene-based cobalt complexes. Issue 13 (13th March 2018) - Lemes, Maykon A.; Magnan, François; Gabidullin, Bulat; Brusso, Jaclyn
Abstract : A hexaazatrinaphtylene-based transition metal complex that exhibits single molecule magnet behaviour is reported herein. This study reveals the influence of both nuclearity and topology on the magnetic properties of hexaazatrinaphtylene-based complexes. Abstract : A hexaazatrinaphtylene-based transition metal complex that exhibits single molecule magnet (SMM) behaviour is reported herein. Both monometallic (1 ) and bimetallic (2 ) Co II complexes with distorted octahedral geometries could be obtained through a straightforward change in synthetic conditions. Field induced SMM behaviour was exhibited by1, with a D value of −60 cm −1 and U eff = 17 K originating from the unquenched orbital angular momentum of the octahedral Co II (d 7 ) centre. On the other hand, 2 exhibits weak antiferromagnetic interactions with a positive D value, thus preventing the observation of SMM behaviour. This investigation reveals the influence of both nuclearity and topology on the magnetic properties of HATN based complexes.